Implementasi Kurikulum Merdeka Dalam Proses Belajar Mengajar di SMP Negeri 1 Kaliorang - Nur Aisyah; Faelasup Faelasup (AL-AMIYAH: Jurnal Ilmiah Multidisiplin, 2024)
Abstract This study examines the implementation of teachers' teaching and learning process in the context of the Independent Curriculum at SMP Negeri 1 Kaliorang. As Indonesia's latest educational innovation, the Independent Curriculum aims to provide greater flexibility and autonomy to teachers and schools in managing learning. This study uses a qualitative approach with a case study method to deeply understand how teachers at SMP Negeri 1 Kaliorang adapt and apply the principles of the Independent Curriculum in their daily teaching practices. Data was collected through classroom observations, in-depth interviews with teachers and principals, and analysis of learning documents. The results show that teachers have begun integrating elements of the Independent Curriculum such as project-based learning, instruction differentiation, and formative assessment. However, there were also some challenges in implementation, including limited resources, the need for ongoing professional development, and the need for adaptation time.